2022
DOI: 10.31004/prepotif.v6i1.3007
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Hypnobirthing, Yoga Dan Senam Hamil Terhadap Tingkat Kecemasan Ibu Hamil Trimester Iii Di PMB Oktaris Kec Sumber Marga Telang

Abstract: Indonesia sebagai negara berkembang masih memiliki angka kematian yang cukup tinggi. Berdasarkan Survei Penduduk Antar Sensus (SUPAS), didapati jumlah AKI di Indonesia pada tahun 2015 sebanyak 305 kasus, Kecemasan pada ibu hamil dapat muncul karena masa panjang saat menanti kelahiran penuh ketidakpastian dan juga bayangan tentang hal-hal yang menakutkan saat proses persalinan. Beban psikologi pada seorang wanita hamil, lebih banyak terjadi pada umur kehamilan trimester III. Olahraga yang dianjurkan pada ibu ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…As an alternative, the research by (Iryani, Pramestigiri, & F, 2022) revealed that employing a birthing ball and endorphin massage therapy during the active period of labor significantly reduced the level of pain. Another investigation corroborated this conclusion (Meliani, Amlah, & Rahmawati, 2022), Research demonstrated that engaging in hypnobirthing, yoga, and pregnancy exercises throughout the third trimester, along with performing breathing techniques while utilizing a birth ball, were all associated with decreased anxiety levels. Furthermore, studies have revealed how effective birth ball exercise is at accelerating the early and second stages of labor.…”
Section: Introductionmentioning
confidence: 73%
“…As an alternative, the research by (Iryani, Pramestigiri, & F, 2022) revealed that employing a birthing ball and endorphin massage therapy during the active period of labor significantly reduced the level of pain. Another investigation corroborated this conclusion (Meliani, Amlah, & Rahmawati, 2022), Research demonstrated that engaging in hypnobirthing, yoga, and pregnancy exercises throughout the third trimester, along with performing breathing techniques while utilizing a birth ball, were all associated with decreased anxiety levels. Furthermore, studies have revealed how effective birth ball exercise is at accelerating the early and second stages of labor.…”
Section: Introductionmentioning
confidence: 73%